A comparative study on preliminary performance evaluation of ATFs under normal and accident conditions with FRAP-ATF code. (May 2018) - Qiu, Bowen; Wu, Yingwei; Deng, Yangbin; He, Yanan; Liu, Tong; Su, G.H.; Tian, Wenxi
Abstract: Accident tolerant fuels (ATFs) are expected to provide better thermal and mechanical performance than a standard UO2 -Zr fuel system, especially in the case of severe accidents. SiC triplex composites and FeCrAl alloys are potential cladding materials that have a high oxidation resistance. In addition, fully ceramic microencapsulated fuel (FCM) pellets are candidates for ATFs due to their high thermal conductivity and capacity to reduce (or contain) the release of fission products. However, ATF materials are still in the research stage and their performance with regard to different types of ATF claddings and pellets under normal and accident conditions require analysis and simulation to determine the optimal combinations of the components. Thus, FRAP-ATF, a modified computer code based on the fuel rod performance analysis codes, FRAPCON 4.0/FRAPTRAN 2.0 was programmed based on investigations of the ATF materials properties from published literatures. The evaluated performance parameters included fuel temperature distribution, cladding stress and strain, the release fraction of fission gas, internal pressure, gap thickness, and the contact stress between the cladding and the pellets. The results indicate that ATF materials have no obvious advantages with regard to the thermal performance except for their excellent oxidation resistance. However, ATFs possess marked advantages under accident conditions and delay the cladding failure effectively. Additional experiments and model modifications are still required to provide further details. Highlights: FRAP-ATF code was developed from FRAPCON4.0/FRAPTRAN2.0 by adding physical models to simulate the performance of ATFs. A non-rigid pellet model and another assumptions were used in the development. Key performance indicators of ATFs were analyzed and compared with UO2 -Zr fuel rod under normal and accident conditions.